An explant technique for high-resolution imaging and manipulation of mycobacterial granulomas. (December 2018) - Cronan, Mark; Matty, Molly; Rosenberg, Allison; Blanc, Landry; Pyle, Charlie; Espenschied, Scott; Rawls, John; Dartois, Véronique; Tobin, David
Abstract A central and critical structure in tuberculosis, the mycobacterial granuloma consists of highly organized immune cells, including macrophages that drive granuloma formation through a characteristic epithelioid transformation. Difficulties in imaging within intact animals and caveats associated with in vitro assembly models have severely limited the study and experimental manipulation of mature granulomas. Here we describe a new ex vivo culture technique, wherein mature, fully organized zebrafish granulomas are microdissected and maintained in three-dimensional (3D) culture. This approach enables high-resolution microscopy of granuloma macrophage dynamics, including epithelioid macrophage motility and granuloma consolidation, while retaining key bacterial and host characteristics. Using mass spectrometry, we find active production of key phosphotidylinositol species identified previously in human granulomas. We also describe a method to transfect isolated granulomas, enabling genetic manipulation, and provide proof-of-concept for host-directed small-molecule screens, identifying protein kinase C (PKC) signaling as an important regulator of granuloma macrophage organization. An ex vivo 3D culture model of mycobacterial granulomas recapitulates the in vivo physiology of these structures and enables longitudinal imaging studies. The platform allows genetic and pharmacological manipulation of this key structure.